Inflammatory burden index predicts long term mortality in a nationally representative population from NHANES - Wenze Li; Defeng Zhao; Wenya Li (Scientific Reports)
Abstract This study investigated the relationship between the Inflammatory Burden Index (IBI) and risks of all-cause and cancer-specific mortality, focusing on its potential to enhance risk stratification. The research included a cohort of 14,835 participants from the American National Health and Nutrition Examination Survey. IBI was calculated using the formula CRP × (neutrophil / lymphocyte). Cox regression analysis was applied to assess the associations. During 223,719.71 person-years of follow-up, 3483 deaths (23.48%) occurred, including 778 (5.24%) from cancer. Mortality rates were 15.57 (all causes) and 3.48 (cancer) per 1,000 person-years. Kaplan–Meier analysis showed the highest IBI quartile had the lowest survival rates for all-cause and cancer-related mortality (Log-Rank p < 0.001). Adjusted models revealed a 23.4% higher risk of all-cause mortality and a 14.1% higher cancer-specific mortality per standard deviation increase in IBI. Smooth curve fitting confirmed a proportional relationship between IBI and mortality risk. ROC curve and reclassification analyses supported IBI’s role in improving mortality risk prediction. The findings of this study indicate noteworthy associations between IBI and both all-cause and cancer-specific mortality. Moreover, the results highlight the potential of IBI in enhancing risk stratification for incident all-cause and cancer-specific mortality within the general population.